Elastic analysis of raft foundations - Hemsley, J. A. (Thomas Telford, 1998)
John Hemsley presents a summary of recent research into the elastic analysis of raft foundations, outlining its potential uses for structural design and covering the fundamental aspects of the subject.
Includes index.
Keywords: Foundations.; Elastic analysis (Engineering); Structural analysis (Engineering); elektronické knihy; electronic books